2004
DOI: 10.1270/jsbbs.54.327
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci (QTLs) Controlling Heading Time in the Population Generated from a Cross between Oriental and Occidental Barley Cultivars (<i>Hordeum vulgare</i> L.)

Abstract: The present study was carried out to identify QTLs controlling heading time of barley. A total of 89 recombinant inbred lines (RILs) generated from a cross between the Oriental-type winter cultivar 'Azumamugi' and the Occidental-type spring cultivar 'Kanto Nakate Gold' were examined. Two field experiments consisting of one spring sowing and one autumn sowing and a greenhouse experiment under 24 h illumination were conducted. Two genes for the spring habit and five QTLs controlling heading time were identified.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…qDHE.ak-7H was expressed in the Ppd-SV treatment, and thus is responsive to the lengthening of the photoperiod as spring advanced. The same QTL was also detected in a spring sowing of non-vernalized barley (Sameri and Komatsuda 2004), which indicates that its action is independent of vernalization. In the Ppd-SNV experiment, the flowering time of the 20 winter habit RILs was greatly delayed, and these were therefore eliminated from the QTL analysis.…”
Section: Flowering Time Genes Detected Under Field Conditionsmentioning
confidence: 57%
See 2 more Smart Citations
“…qDHE.ak-7H was expressed in the Ppd-SV treatment, and thus is responsive to the lengthening of the photoperiod as spring advanced. The same QTL was also detected in a spring sowing of non-vernalized barley (Sameri and Komatsuda 2004), which indicates that its action is independent of vernalization. In the Ppd-SNV experiment, the flowering time of the 20 winter habit RILs was greatly delayed, and these were therefore eliminated from the QTL analysis.…”
Section: Flowering Time Genes Detected Under Field Conditionsmentioning
confidence: 57%
“…Sameri and Komatsuda (2004) found a close linkage between sgh1 and e04m32.8. Here, the Ppd-SNV treatment detected a QTL lying close to vrn-H2.…”
Section: Vernalization Response Genesmentioning
confidence: 84%
See 1 more Smart Citation
“…Laurie et al (1995) reported that 4 genes and 8 QTLs were involved in controlling the timing of flowering in autumn-sowing, spring-sowing and glasshouse experiments using doubled-haploid (DH) lines developed from a cross between the winter barley variety Igri and the spring variety Triumph. Autumn-sowing and spring-sowing experiments using recombinant inbred lines (RILs) from the winter variety Azumamugi and the spring variety Kanto Nakate Gold identified a total of 7 QTLs (Sameri and Komatsuda 2004). Figure 1 shows the QTLs and the mapping of the positions of the photoperiodic and vernalization response genes of barley, according to Laurie et al (1995) and Sameri and Komatsuda (2004).…”
Section: Qtl Analyses For the Photoperiodic Control Of Flowering In Bmentioning
confidence: 99%
“…Franckowiak and Konishi (2002) identified the Eam6 locus on chromosome 2HS, which might be synonymous with the eps2 locus identified by Laurie et al (1995). Recently, a QTL on chromosome 1H was located at the interval between ABC261 and ABG055 markers controlling heading time from the Azumamugi (JP17209)  Kanto RIL population, which is supposedly closely linked or allelic to eam8 (Sameri and Komatsuda 2004;Sameri et al 2006). However, comparing our mapping results with the barley consensus map, ABC261 and ABG055 markers were not entirely consistent with the BVP-1 gene closely-linked markers in this study.…”
Section: Mot1-m9 Polymorphic Marker Is 794 Bp Downstream From Thementioning
confidence: 99%